2012
DOI: 10.1002/ptr.4703
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Regulates Apoptotic Pathway in Human Liver Cancer Cells

Abstract: Emodin, a natural anthraquinone, has been reported to possess antiproliferative effects in many cancer cell lines. However, anticancer mechanism against human liver cancer remains unclear. In this study, we observed that emodin induced apoptosis in HepG2 cells and caused a significant accumulation of cells in the G1 phase. Western blot data showed that emodin treatment caused the increasing of release of cytochrome c into cytosol from mitochondria and the activation of caspase-8 and caspase-9, which suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Study on hepatocarcinoma cells Huh7, Hep3B, and HepG2 revealed that treatment of emodin retards NF-jB/p65 protein level, and Bcl-2 expression, with simultaneous increase in p53 levels. It releases mitochondrial cytochrome C and also activates caspase-8 and -9 [69].…”
Section: Reported Effects On Apoptosismentioning
confidence: 99%
“…Study on hepatocarcinoma cells Huh7, Hep3B, and HepG2 revealed that treatment of emodin retards NF-jB/p65 protein level, and Bcl-2 expression, with simultaneous increase in p53 levels. It releases mitochondrial cytochrome C and also activates caspase-8 and -9 [69].…”
Section: Reported Effects On Apoptosismentioning
confidence: 99%
“…Emodin induces apoptosis of the HeLa human cervical cell line by activation of the mitochondria apoptotic pathway (46). Cancer cell apoptosis also can be induced by emodin in the HepG2 human HCC cell line through activation of the p53 pathway and inhibition of the NF-κB/p65 pathway (47).…”
Section: Anthraquinonementioning
confidence: 99%
“…1A), an active monomer extracted from Rheum, Polygonum, Buckthorn and Senna, has been shown to be active against pancreatic (5,6), lung (7,8), breast (9,10), liver (11), prostate (12,13), ovarian (14), cervical (15), colon (16), gallbladder (17) and human tongue cancer SCC-4 cells (18,19). Moreover, it has been reported that emodin induces apoptosis of human breast cancer MCF-7 (20) and MDA-MB-453 cells (21).…”
Section: Introductionmentioning
confidence: 99%